2009
DOI: 10.1183/09031936.00110109
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and outcome of pulmonary fibrosis in microscopic polyangiitis

Abstract: We sought to determine the type of pulmonary involvement in microscopic polyangiitis (MPA), primarily focusing on pulmonary fibrosis (PF), its prevalence, temporal relationship with other disease manifestations and outcome.33 patients (16 males) with biopsy proven perinuclear anti-neutrophilic cytoplasmic antibodypositive MPA (age 63.5 yrs) participated in the study. Pulmonary involvement was assessed using standard methods, including radiographic imaging (chest radiographs and high-resolution computed tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
151
4
16

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(177 citation statements)
references
References 26 publications
6
151
4
16
Order By: Relevance
“…Although this has been previously reported in the literature (4,5,7,8,(27)(28)(29)(30)(31), we analyzed CT images in sequential hospital-based patients before they received treatment and determined the prevalence of each imaging component of ILD (Table 2). Ground-glass opacity was the most prevalent component, which indicates that a large proportion of MPA patients have an active inflammatory process in the lungs before they receive treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this has been previously reported in the literature (4,5,7,8,(27)(28)(29)(30)(31), we analyzed CT images in sequential hospital-based patients before they received treatment and determined the prevalence of each imaging component of ILD (Table 2). Ground-glass opacity was the most prevalent component, which indicates that a large proportion of MPA patients have an active inflammatory process in the lungs before they receive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Diffuse alveolar hemorrhage (DAH) is a well-described pulmonary manifestation of small vessel vasculitis (3,6). However, interstitial lung disease (ILD) was recently recognized as a major pulmonary manifestation in patients with MPA (7,8), although its pathogenesis remains largely unknown. Even more intriguingly, a previous histopathologic analysis showed that a wide variety of extravascular pulmonary injuries, including airway lesions, can be observed in patients with AAVs (9).…”
mentioning
confidence: 99%
“…Although ANCA panel positivity has been reported with interstitial pneumonia (and usual interstitial pneumonia (UIP) pattern disease in particular) and may reflect microscopic polyangiitis or another vasculitic disease [43,44], these autoantibodies are not included in the serologic domain because they are associated with the vasculitides, rather than the CTD-ILD spectra of disorders.…”
Section: Serologic Domainmentioning
confidence: 99%
“…It is known that diffuse alveolar hemorrhage is mainly due to alveolar capillaritis; however, the pathogenesis of IP remains unclear [1]. Recurrent occult alveolar hemorrhage has been suggested as a putative mechanism leading to pulmonary fibrosis in patients with ANCA-associated vasculitis [9]. Alternatively, the authors of several studies have suggested that MPO antibodies may cause pulmonary tissue injury through the release of products of activated neutrophils [10].…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that the SP-D level may have been a sensitive marker of IP disease activity in our patient. Takahashi et al [9] demonstrated that SP-D is more useful than SP-A in detecting interstitial lung disease in patients with progressive systemic sclerosis. Since the serum MPO-ANCA remained negative in our patient when her IP deteriorated, the serum MPO-ANCA level may not be a reliable marker for monitoring disease activity in the lungs.…”
Section: Discussionmentioning
confidence: 99%